Novel [FeFe]-Hydrogenase Mimics: Unexpected Course of the Reaction of Ferrocenyl α-Thienyl Thioketone with Fe3(CO)12 † - Daraosheh, Ahmad Q.; Abul-Futouh, Hassan; Murakami, Natsuki; Ziems, Karl Michael; Goerls, Helmar; Kupfer, Stephan; Gräfe, Stefanie; Ishii, Akihiko; Celeda, Malgorzata; Mloston, Grzegorz; Weigand, Wolfgang (Materials, 2022)
The influence of the substitution pattern in ferrocenyl α-thienyl thioketone used as a proli-gand in complexation reactions with Fe3 (CO)12 was investigated. As a result, two new sulfur–iron complexes, considered [FeFe]-hydrogenase mimics, were obtained and characterized by spectroscopic techniques (1H,13C1H NMR, IR, MS), as well as by elemental analysis and X-ray single crystal diffraction methods. The electrochemical properties of both complexes were studied and compared using cyclic voltammetry in the absence and in presence of acetic acid as a proton source. The performed measurements demonstrated that both complexes can catalyze the reduction of protons to molecular hydrogen H2 . Moreover, the obtained results showed that the presence of the ferrocene moiety at the backbone of the linker of both complexes improved the stability of the reduced species.
CRIS-Team Scopus Importer:2023-04-20
Keywords: cyclic voltammetry; dearomatization; ferrocenyl thioketones; heteroaryl thioketones; hydrogenase active centers mimics; iron carbonyls; reaction mechanisms; sulfur–iron clusters; X-ray diffraction analysis